P15 Resuming antiplatelet and anticoagulant therapy following isolated traumatic brain injury in adults: a national survey and review of literature. Issue 3 (14th February 2019) - Valenzuela, T; Fellows, D; Zaben, M; Shastin, D; Leach, P
Abstract : Objectives: Antithrombotics use in the elderly is widespread and is seen as a risk factor for intracranial complications following TBI. Antithrombotics are commonly discontinued on admission, with little guidance on when or how to restart them. This study aims to establish current national practices with restarting antithrombotic medications following TBI and review available evidence identifying areas for further research. Design: An online survey and a literature review. Subjects: SBNS members. Methods: A SBNS Academic Committee approved survey with five TBI scenarios dealing with different antithrombotics. Respondents were asked to indicate when they would restart the medications for each scenario and what drives their decision. Results: Preliminary results included responses from 22 consultants. The most common practice was to restart antithrombotics after two weeks; however, less than 50% agreed on each individual option. About 50% had the same approach to everything and 1/3 believed single antiplatelet can be resumed earlier than dual antiplatelets. Other deciding factors included size of intracranial bleed, patient's neurological recovery, and follow up imaging. Some advocated involving the physicians. Final results following a repeat dissemination of the survey will be presented at the meeting. Conclusions: There is obvious discrepancy in how the problem of restarting antithombotics following TBI is approached nationally. Further research is needed to help decision making with this everyday clinical problem.